2011
DOI: 10.1021/ja207160z
|View full text |Cite
|
Sign up to set email alerts
|

Hyperaromatic Stabilization of Arenium Ions: A Remarkable Cis Stereoselectivity of Nucleophilic Trapping of β-Hydroxyarenium Ions by Water

Abstract: Cis- and trans-1,2-dihydrodiol isomers of benzene undergo acid-catalyzed dehydration to form phenol. In principle the isomeric substrates react through a common β-hydroxybenzenium (cyclohexadienyl) carbocation. Notwithstanding, the isomers show a large difference in reactivity, k(cis)/k(trans) = 4500. This difference is reduced to k(cis)/k(trans) = 440 and 50 for the 1,2-dihydrodiols of naphthalene and 9,10-dihydrodiols of phenanthrene, respectively, and to 6.9 for the dihydrodiols of the nonaromatic 7,8-doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 40 publications
1
22
1
Order By: Relevance
“…However, these substituents also gave partial rearrangement, with formation of 1-as well as 2-substituted naphthalene products. 4 For the cis isomers it seems likely that the rearrangement must follow formation of the β-hydroxynaphthalenium ion intermediate and thus does not affect its rate of formation. In the case of the trans isomers rearrangement probably accompanies formation of the carbocation.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these substituents also gave partial rearrangement, with formation of 1-as well as 2-substituted naphthalene products. 4 For the cis isomers it seems likely that the rearrangement must follow formation of the β-hydroxynaphthalenium ion intermediate and thus does not affect its rate of formation. In the case of the trans isomers rearrangement probably accompanies formation of the carbocation.…”
Section: ■ Resultsmentioning
confidence: 99%
“…This is supported by computational results and calculations of ring currents for arenium ions described in a following paper. 4 An obvious question arises that will be addressed in the present paper. What is the consequence of extending the range of 2-substituents from hydroxyl to other possibilities that can be envisaged?…”
Section: ■ Introductionmentioning
confidence: 99%
“…More importantly, HA helps people understand and explains some typical reactivity. For example, O’Ferrall and co-workers once correlated the HA in arenium intermediates with the enhancement of dehydration reaction rates of diols 12,13 . Recently, Houk and co-workers revealed that the reactivity and stereoselectivity of 5-substituted cyclopentadienes in Diels–Alder reactions are also related to HA 1416 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we decided to examine a one-pot urazole hydrolysis/bicyclic hydrazine oxidation sequence that would generate dihydrodiols via the extrusion of molecular dinitrogen. Although the hydrolysis and oxidation sequence was expected to be reasonably straightforward, the lability of such dihydrodiols was potentially troublesome 21,32 . Indeed, this turned out to be the case, as we observed significant amounts of phenol formation during the oxidation step.…”
Section: Resultsmentioning
confidence: 99%